2005
DOI: 10.1111/j.1365-2265.2005.02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in the MEN1 gene in subjects with multiple endocrine neoplasia‐1

Abstract: We have identified four novel mutations in the MEN1 gene in patients with MEN1 in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In many recent studies, novel MEN1 gene mutations were reported (21,22). Novel missense mutations accounted for 15% of the total mutations, and the possibility that a novel splice donor mutation, as in our case, is a rare nonpathogenic event cannot be excluded.…”
Section: Discussionmentioning
confidence: 50%
“…In many recent studies, novel MEN1 gene mutations were reported (21,22). Novel missense mutations accounted for 15% of the total mutations, and the possibility that a novel splice donor mutation, as in our case, is a rare nonpathogenic event cannot be excluded.…”
Section: Discussionmentioning
confidence: 50%
“…Most of the previous studies were case reports with the biggest sample size of 12 patients (6 sporadic and 6 familial cases) [20]. In all reported cases, 31 MEN1 mutations were detected in 32 MEN1 families (96.9%) and 3 MEN1 mutations were reported in 6 sporadic MEN1 patients (50%)[8, 9, 2028]. Sporadic MEN1 cases were included in only one of these studies [20], which suggests that selection and publication bias might be present and therefore, real MEN1 mutation rate could not be accurately calculated from these studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, little is known about the clinical spectrum and genetic background of MHPT patients in China [8, 9]. Therefore, we compared the clinical characteristics of MHPT to those of SHPT in Chinese patients using a relatively large sample size and included details on severity of the disease, biochemical parameters and radiographic results.…”
Section: Introductionmentioning
confidence: 99%
“…Since the cloning of the MEN1 gene, genetic screening of patients/families with MEN1 has been performed extensively in Europe, 10,28–30 North America 3,11,20 and Australia, 31,32 and less extensively in Asia 33,34 . Analysis of multiethnic cohorts with MEN1 can more precisely define the clinical and genetic features of this complex syndrome.…”
Section: Discussionmentioning
confidence: 99%